Effects of 7.5% Carbon Dioxide and Nicotine Administration on Latent Inhibition - Granger, Kiri T.; Ferrar, Jennifer; Caswell, Sheryl; Haselgrove, Mark; Moran, Paula M.; Attwood, Angela; Barnett, Jennifer H. (Frontiers in Psychiatry, 2021)
Stratified medicine approaches have potential to improve the efficacy of drug development for schizophrenia and other psychiatric conditions, as they have for oncology. Latent inhibition is a candidate biomarker as it demonstrates differential sensitivity to key symptoms and neurobiological abnormalities associated with schizophrenia. The aims of this research were to evaluate whether a novel latent inhibition task that is not confounded by alternative learning effects such as learned irrelevance, is sensitive to 1) an in-direct model relevant to psychosis (using 7.5% carbon dioxide (CO₂) inhalations to induce dopamine release via somatic anxiety) and 2) a pro-cognitive pharmacological manipulation (via nicotine administration) for the treatment of cognitive impairment associated with schizophrenia. Experiment 1 used a 7.5% CO₂ challenge as a model of anxiety-induced dopamine release to evaluate the sensitivity of latent inhibition during CO2 gas inhalation, compared to the inhalation of medical air. Experiment 2 examined the effect of 2mg nicotine administration versus placebo on latent inhibition to evaluate its sensitivity to a potential pro-cognitive drug treatment. Inhalation of 7.5% CO2 raised self-report and physiological measures of anxiety and impaired latent inhibition, relative to a medical air control; whereas administration of 2mg nicotine, demonstrated increased latent inhibition relative to placebo control. Here, two complementary experimental studies suggest latent inhibition is modified by manipulations that are relevant to the detection and treatment of schizophrenia. These results suggest that this latent inhibition task merits further investigation in the context of neurobiological sub-groups suitable for novel treatment strategies.